Legal Frameworks and Agronomic Innovations: Impact of Climate Change on Food Security Laws and the Role of Climate-Resilient Crops in India (International Journal of Food and Nutritional Sciences, 2022)
Even though food security laws exist, with one of the prime legislations being the National Food Security Act (NFSA), 2013, Indian legal frameworks are nevertheless not fully inclined to integrating climate change risk into their design and implementation. Thus, the present food security framework does not adequately address the emerging threats posed by climate variability and thus remains limited in its capability to safeguard food security in a changing environment. And while agronomic innovations like climate-resilient crops have shown promise in reducing those risks, their uptake remains patchy because of regulatory, financial, and awareness limitations. Thus, the linkages between legal frameworks and agronomic developments in the Indian context need to be examined in current times.